P86 The assessment of health related quality of life in sarcoidosis with the King's Sarcoidosis Questionnaire (KSQ). (2nd December 2011) - Patel, A S; Siegert, R; Creamer, D; Larkin, G; Gray, B; Wells, A U; Higginson, I J; Birring, S S
Abstract : Introduction: The King's Sarcoidosis Questionnaire (KSQ) is a recently developed and validated sarcoidosis specific health related quality of life (HRQOL) tool comprising of 5 modules: general HRQOL (10 items), lung (6 items), medication/side-effects (3 items), skin (4 items), and eye (7 items). We set out to evaluate HRQOL in a large group of patients with wide ranging sarcoidosis and determine the factors that influence it. Methods: 207 patients with sarcoidosis (89% lung, 26% skin, 22% eye, 29% other organ involvement) attending outpatient clinics at King's College and Royal Brompton Hospitals completed the KSQ. KSQ domain scores range from 0 to 100, a higher score representing a better HRQOL. Demographic data, immunosuppressant medication, organ involvement, lung function, Scadding CXR stage, physicians global assessment (PGA) of severity of skin disease and visual acuity (VA) were recorded. Results: Patients had a mean (SEM) age 48 (11) years, 54% were female and 30% were Afro-Caribbean. Patients had a mean (SEM) FEV1 80 (23)% predicted, FVC 94 (19)% predicted and TLCO % predicted 66 (17). HRQOL was impaired in all domains, mean (SEM) scores: general HRQOL 51 (2), lung 61 (2), medication/side-effects 49 (3), skin 54 (4), and eye 50 (4). Patients with 2 or more organ involvement compared to single organ involvement had worse general HRQOL (44 (3) vs 58 (3); p<0.01) and worse medication/side-effects scores (44 (3) vs 58 (3); p=0.04). Female patients compared to males had worse general HRQOL (45 (3) vs 57 (3); p<0.01) and medication/side-effects scores (41 (3) vs 58 (4); p<0.01). There were no associations between HRQOL and age (r=−0.02 to 0.13) or ethnicity (p=0.42). There was a weak but significant relationship between lung HRQOL and FEV1 (r=0.38, p<0.01), FVC (r=0.38, p<0.01) and TLCO % predicted (r=0.22, p<0.01). Patients with Scadding CXR stage 3–4 disease compared to stage 0–2 disease had significantly worse lung HRQOL (51 (4) vs 63 (3); p=0.02). Skin health was associated with physician's global assessment (PGA) of severity of skin disease (r=0.51, p<0.01). Eye health was associated with VA (r=−0.56, p<0.01). Patients taking immunosuppressant medication for sarcoidosis compared to those not taking immunosuppresants had significantly worse general HRQOL (45 (2) vs 66 (4); p<0.01) and lung HRQOL scores (58 (3) vs 70 (4); p=0.01). Conclusions: HRQOL is impaired in sarcoidosis. Gender, immunosuppressant medication, multi-system organ involvement and severity of lung function impact on HRQOL. This study provides further clinical validation of the KSQ.